Development of self-assembled poly(2-ethyl-2-oxazoline)-b-poly(ε-caprolactone) (PEtOx-b-PCL) copolymeric nanostructures in aqueous solution and evaluation of their morphological transitions - U. U. Ozkose; S. Gulyuz; U. C. Oz; M. A. Tasdelen; O. Alpturk; A. Bozkir; O. Yilmaz (eXPRESS Polymer Letters)
Amphiphilic block copolymers are known to self-assemble into various morphologies, including ellipsoids, tubular structures, toroids, vesicles, micellar structures. In this paper, we discuss the synthesis of copolymeric nanostructures (CNs) using poly(2-ethyl-2-oxazoline)-block-poly(ε-caprolactone) (PEtOx-b-PCL) amphiphilic block copolymers. Our data indicate that - varying the molecular weight and the number of repeating units dictate the nature of morphology. That is, the formation of self-assembled morphologies from ellipsoid to rod-like architectures are observed in aqueous solution, depending on the mass ratio of the hydrophilic block (fPEtOx). To best of our knowledge, this is the first report on the morphological transitions of PEtOx-b-PCL amphiphilic block copolymer-based CNs with different fPEtOx values in the literature.